2020
DOI: 10.3390/plants9111419
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Responses of Canola to Exogenous Application or Endogenous Overproduction of 5-Aminolevulinic Acid (ALA) under Various Nitrogen Levels

Abstract: Limited data are available on the effects of 5-aminolevulinic acid (ALA) on plant photosynthesis in relation to the nitrogen (N) level. In this study, we investigate photosynthetic responses to ALA in canola plants (Brassica napus L.). We used wild-type plants without ALA addition (controls), wild-type plants with exogenous ALA application, and transgenic plants that endogenously overproduced ALA. The plants were grown hydroponically in nutrient solutions with low, middle, and high concentrations of N. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(87 reference statements)
2
8
0
Order By: Relevance
“…In addition to research on exogenous ALA application, studies on transgenic plants that overproduce endogenous ALA have confirmed its biological functions. When Yhem1 (a yeast Hem1 driven by the Arabidopsis HemA promoter, which is light-inducible) was transformed into higher plants, transgenic tobacco [ 76 , 77 ], strawberry [ 78 ], tomato [ 79 ], and canola [ 80 ] biosynthesized much more endogenous ALA and chlorophyll and had higher photosynthetic rates and energy conversion efficiency than their respective WTs. Yhem1 transgenic Arabidopsis [ 81 ], tomato [ 82 ], and canola [ 83 ] have been demonstrated to be more salt tolerant, and transgenic banana was colder tolerant [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to research on exogenous ALA application, studies on transgenic plants that overproduce endogenous ALA have confirmed its biological functions. When Yhem1 (a yeast Hem1 driven by the Arabidopsis HemA promoter, which is light-inducible) was transformed into higher plants, transgenic tobacco [ 76 , 77 ], strawberry [ 78 ], tomato [ 79 ], and canola [ 80 ] biosynthesized much more endogenous ALA and chlorophyll and had higher photosynthetic rates and energy conversion efficiency than their respective WTs. Yhem1 transgenic Arabidopsis [ 81 ], tomato [ 82 ], and canola [ 83 ] have been demonstrated to be more salt tolerant, and transgenic banana was colder tolerant [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chl. contents were increased in plants grown under middle and high N conditions as compared with plants grown under low N conditions, which significantly affected photochemical processes 20 . N is a fundamental element for leaf plants, insufficient N supply lead to decreased photosynthetic rate in plants 21 , this occurs to many factors such as a decrease in pigment degradation 22 , reduction in stomatal conductance 23 and a decline in the light and dark reaction of photosynthesis.…”
Section: Resultsmentioning
confidence: 96%
“…Canola is a nitrophilous plant, wherein a high concentration of NO 3 in the culture media results in higher Chl. contents in the plant leave compared with controls 20 . The Chl.…”
Section: Resultsmentioning
confidence: 98%
“…This weight gain could be attributed to the enhanced metabolic activity and improved nutrient assimilation facilitated by the biostimulants 19 . Considering the role of AOS in eliciting defense responses 20 and improving plant vigor 21 , and the influence of 5-ALA on chlorophyll production and energy transfer, it is plausible that these substances improved the photosynthetic efficiency of the plants 22 , thereby leading to an accumulation of biomass. Such findings are particularly significant for the agricultural sector, as they suggest a feasible strategy for increasing yield without compromising, and potentially improving, the quality of the produce.…”
Section: Discussionmentioning
confidence: 99%